Joint exposure to PM2.5, warm-season heat, and sedentary behavior accelerates incident lung cancer in ageing Chinese adults: evidence from CHARLS - Wang, Yang-Zhong; Tang, Nan; Tao, Tao; Peng, Xian-Lin (Frontiers in Public Health, 2025)
ObjectiveJoint exposure to fine particulate matter (PM₂․₅) and prolonged sedentary behavior in later life may erode physiological reserve and hasten carcinogenesis, yet evidence quantifying their combined impact on incident lung cancer among older Chinese adults is sparse. We investigated whether co-occurrence of high ambient PM₂․₅ and extensive sitting time accelerates incident lung cancer in a nationally representative cohort.MethodsWe analyzed 10,532 adults aged ≥45 years in the China Health and Retirement Longitudinal Study (2011–2018). Chronic PM₂․₅ exposure was assigned from a satellite–chemistry–model product and classified into sex-specific tertiles; daily sitting time was self-reported and dichotomised at ≥8 h day−1. Eight joint-exposure categories crossed environmental burden (low/low, high PM₂․₅ only, high heat only, high/high) with sedentary status (low vs. high). Weighted Cox models with age as the time axis estimated hazard ratios (HRs) for incident lung cancer; additive interaction was assessed via relative excess risk due to interaction (RERI) and synergy index (S).ResultsOver 43,181 person-years, 141 incident lung-cancer cases were recorded (3.3 per 1,000 person-years). Independently, high PM₂․₅ (HR 1.82, 95% CI 1.29–2.57) and high sedentary time (HR 2.10, 95% CI 1.55–2.84) increased risk. Participants simultaneously exposed to high PM₂․₅, high warm-season heat, and ≥8 h sitting exhibited a nearly five-fold hazard (HR 4.95, 95% CI 2.24–10.95) versus the dual-low reference. Additive interaction was evident (RERI 1.10, synergy index 1.39), and associations were most pronounced in men and rural residents. Sensitivity analyses varying sedentary thresholds, excluding early events, and applying competing-risk models yielded consistent findings.ConclusionConcurrent high ambient PM₂․₅ and prolonged sedentary behavior markedly accelerate incident lung cancer in middle-aged and older Chinese adults, with evidence of biologic synergy beyond independent effects. Integrated interventions that couple aggressive air-quality regulation with strategies to curtail sedentary time—particularly among socio-economically disadvantaged and rural populations—are warranted to mitigate China’s looming lung-cancer burden in an aging society.